Efektifitas Media Pembelajaran Pada Pendekatan Scientific terhadap Literasi Sains dan Self Efficacy Peserta Didik SDN 193 Pekanbaru - Desri Ana Sovia; Yayuk Cicilia; Rian Vebrianto (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
This study aims to determine the effect of the use of media the influence of the science learning media on a scientific approach to scientific literacy skills and self-efficacy of students on human respirator material. This study uses an experimental method, the sample consists of 2 classes, cognitive learning achievement data using tests, affective aspects of learning achievement using a questionnaire, hypothesis testing using the right-hand t-test. The data analysis technique used is the n-gain test and independent sample t-test using SPSS version 16.0. The results showed that students who were taught using science learning media on a scientific approach had a good effect on scientific literacy and self efficacy better than students who were taught the lecture method. Students with high scientific literacy ability produce better average performance than students with low scientific literacy ability, and there is an increase in the self efficacy of students learning by using learning media